A National‐Level Informational Experiment to Promote Enrollment in Selective Colleges. (9th October 2020) - Gurantz, Oded; Howell, Jessica; Hurwitz, Michael; Larson, Cassandra; Pender, Matea; White, Brooke
Abstract: Prior research finds that low‐income students are less likely to apply to and enroll in four‐year colleges or more selective colleges, even after controlling for academic preparation and other background characteristics. The College Board sought to reduce barriers in the college application process through a targeted campaign of brochures and e‐mails. These materials were sent to students two to three times between the end of eleventh grade and the middle of twelfth grade, and aimed to provide an impetus to start the college search process, minimize the costs of aggregating data, and encourage a broader college application portfolio. Some students were offered additional encouragements, such as text message reminders or college application fee waivers. In a randomized control trial with 785, 000 low‐ and middle‐income students in the top 50 percent of the PSAT and SAT distributions, we find no changes in college enrollment patterns.